(untitled) (ItalianoLinguadue, 2009)
Il contributo, incentrato sul tema dell’italianismo in prospettiva lessicografica tra storia, etimologia e cultura, tocca i problemi della durata del prestito italiano in francese, delle motivazioni che lo hanno generato, della funzione mediatrice che lo caratterizza, dell’estensione semantica in sincronia e diacronia e dell’aspetto derivazionale. The article focuses on Italianisms from a lexicographical perspective embracing history, etymology and culture and involving issues related to the duration of borrowings from Italian in French, the motives that generated it, the mediating function by which it is characterized, its semantic range, both synchronic and diachronic, and the aspect of derivations.